Characterisation and optimisation of the mechanical performance of plant fibre composites for structural applications - Shah, Darshil Upendra (2013)
Plant fibres, perceived as environmentally sustainable substitutes to E-glass, are increasingly being employed as reinforcements in polymer matrix composites. However, despite the promising technical properties of cellulose-based fibres and the historic use of plant fibre composites (PFRPs) in load-bearing components, the industrial uptake of PFRPs in structural applications has been limited. In developing PFRPs whose mechanical properties are well-characterised, optimised and well-predicted, this thesis addresses the question: Can PFRPs replace E-glass composites (GFRPs) in structural applications?